CHLOROPHYLL SPECIFIC ABSORPTION COEFFICIENTS AND THE IMPACT OF PHYTOPLANKTON TAXONOMIC GROUP OF SURFACE WATERS IN THE NORTHEASTERN GULF OF MEXICO - Bisman Nababan (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2009)
The chlorophyll-specific absorption coefficient at 440 nm (a*ph(440)) of surface water in the Northeastern Gulf of Mexico varied by a factor of 7 (0.02-0.15 m2 mg-1) with the of chlorophyll-a concentration of 0.06-12.25 mg m-3. In general, lower values of a*ph(440) (<0.06 m2 mg-1) were observed in the inshore particularly in the major river mouths. During summer, lower values of a*ph(440) were also observed offshore associated with low-salinity waters of the Mississippi River plume. Higher values of a*ph(440) (>0.1 m2 mg-1) were otherwise observed outside the river plumes in the outershelf and slope, where lower chlorophyll-a concentration occurred. Based on phytoplankton taxonomic groups, the average value of a*ph(440), of microphytoplankton group was significantly lower than that of nanophytoplankton and picophytoplantkon groups, suggesting that an increase in cell optical size (pigment packaging) resulted in decreasing a*ph(440) values. The relationship between a*ph(440) and chlorophyll-a concentration was also not linear, indicating pigment composition played an important role in determining a*ph(440) variability.Keywords: chlorophyll-specific absorption coefficient, microphytoplankton, nanophytoplankton,picophytoplankton, Gulf of Mexico, pigment, packaging effect